Organic Substance in the Soil of the Celje Basin Area - Petauer, Milena (Journal for Geography, 2007)
The quantity of the organic substance is an important indicator of the soil quality. It has a significant influence on numerous physical and chemical soil properties; and consequently also on the fertility of the soil and it determines the function of the soil in the ecosystem. The quantity of the organic substance in the soil depends upon the quantity the organic substances which died away, their composition, process of humification, natural factors such as the climate, relief, parent foundation, and water and of course live plants, animals and microorganisms which live in the soil and also upon the use of the soil. In the contribution is represented the quantity of the organic substances in the upper layer of rural surfaces in Slovenia and the quantity of organic substances in the horizon of the prevailing types of soil in the Celje Basin. The data show that the quantity of the organic substance in the soil in Slovenia is satisfactory. The soil in the Celje Basin have less than 6% of organic substance; the differences in the content are mostly shown in the use of the soil because the soils covered with wood have also to 35% of the organic substance in the upper horizon.